1981
DOI: 10.1021/j150622a002
|View full text |Cite
|
Sign up to set email alerts
|

Direction of the dipole moment in the ester group

Abstract: The directions of the dipole moments in esters RCOOR' in which R and R' are alkyl or aryl groups have been deduced by analysis of experimental values of dipole moments of six compounds containing two polar groups, one or both of which are esters. New determinations of molecular dipole moments are reported for dimethyl truns-1,4-cyclohexanedicarboxylate and for truns-l,4-cyclohexanediol diacetate. The moment of the ester group is directed (in the positive sense) at an angle 73 = 123 f 3" from the R-CO axis in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 3 publications
5
83
1
1
Order By: Relevance
“…(2) gives 4.8 Debye (1 D ¼ 3.336 Â 10 À30 As m) for the rigid main chain polymer 2 and 18.4 D for both 4 and 6 at 220 K. The estimated dipole value for 4 and 6 is too high to be accounted for only by an ester group relaxation. The magnitude of the dipole moment of the ester group is in the range 1.65e1.80 D [49,50], which is closer to the estimated values of polymer 2 than for 4 and 6. With the side chain attached at R 1 , phenyl ring mobility is hindered.…”
Section: The B-processsupporting
confidence: 66%
“…(2) gives 4.8 Debye (1 D ¼ 3.336 Â 10 À30 As m) for the rigid main chain polymer 2 and 18.4 D for both 4 and 6 at 220 K. The estimated dipole value for 4 and 6 is too high to be accounted for only by an ester group relaxation. The magnitude of the dipole moment of the ester group is in the range 1.65e1.80 D [49,50], which is closer to the estimated values of polymer 2 than for 4 and 6. With the side chain attached at R 1 , phenyl ring mobility is hindered.…”
Section: The B-processsupporting
confidence: 66%
“…3, 1983 However, it has been shown by measurement of dipole moment that both cis and trans forms are likely to exist in the liquid state of PET. 5 3 Also, Saiz et a/., 54 from a consideration of Coulombic interactions between ester groups ofDMT, concluded that the statistical weight of the cis form is 0.92 relative to the trans form. Moreover, Lowe et a/.…”
mentioning
confidence: 99%
“…This is in agreement with the previous studies employing coulombicenergy calculations. [17] For (f 2 , f 3 ), the energy barrier for the transition between two minima is found to be 5.24 kcal Á mol À1 . The rotational states corresponding to f 5 (f 7 ) are 5 and 958, with the former torsional state at a slightly higher energy value by 0.16 kcal Á mol À1 .…”
Section: Ris Model For Cbdomentioning
confidence: 93%
“…Flory and coworkers have reported that the sterically favored conformations for the dimethyl trans-cyclohexane-1,4-dicarboxylate molecule is one in which the ester groups are coplanar with the axial C-H bonds. [17] Since the cyclohexylenedicarboxylate linkage is in the trans configuration, the torsional value at the f 3 bond is 08. Statistical weight matrices for the bonds relating to the cyclohexanedimethanol fragment are similar to those of PCT, where the trans and cis configurations of the cyclohexanedimethanol group are included (Figure 3).…”
Section: Ris Model For Pccmentioning
confidence: 99%